Original paperPrevalence of cardiovascular disease risk factors, and metabolic syndrome and its components in patients with psoriasis aged 30 to 49 years - Owczarczyk-Saczonek, Agnieszka B.; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Some studies show that metabolic syndrome (MS) is more common in psoriatic patients. Aim : To evaluate the prevalence of MS and its components as cardiovascular disease (CVD) risk factors in psoriatic patients compared to the general Polish population. Material and methods : In 62 patients, aged 30 to 49 years with a mild to severe course of psoriasis, the features of MS have been assessed by IDF definition and compared to the results obtained in the NATPOL 2011 study. Results : Analysis of CVD risk factors in patients with a severe course of psoriasis showed a correlation with waist circumference (0.38, p < 0.05), hypertension (0.40, p < 0.05) and a negative correlation with HDL (0.29, p 0.05), the mean HOMA-IR was 1.93 and 1.94 (p > 0.05), respectively. There were differences in the prevalence of abdominal obesity (53.6% vs. 40.3%, p 130/85 mm Hg) and hypertension were more frequent in men with psoriasis than in the control group (38.2% vs. 11.1%, p < 0.05). Conclusions : Severe psoriasis is associated with a significantly higher prevalence of risk factors for CVD. The prevalence of MS, insulin resistance and lipid abnormalities in patients with psoriasis aged 30 to 49 years is similar to the general Polish population. Abdominal obesity is more common in psoriatic patients and hypertension in men with psoriasis.